Well-Organized MZT-ME-PML Approach for THz BP Metasurface Implementations (Communications in Computational Physics, 2020)
Via adopting the matrix exponential (ME) approach, efficient and tightcomplex-frequency-shifted perfectly matched layer (CFS-PML) formulations using thematched Z-transform (MZT) method are well organized and proposed to truncate themonolayer black phosphorous (BP) metasurface problems in the infrared regime. Dueto introducing ME approach, the proposed MZT-ME-PML develops into the compactfirst-order differential matrix form used to the circumvent convolution manipulations,the variable replacements, or the formulation rearrangements during the mathematicalderivations. Furthermore, the MZT-ME-PML can not only flexibly truncate arbitrarymaterials due to using the DB constitutive relation, but efficiently attenuate evanescent waves and reduce late-time reflections with the CFS scheme. Besides, in view ofthe discretization effect on Terahertz (THz) BP metasurface implementation, the MZTtechnique is added deliberately into this proposal in that it is more suitable for simulating fine structures. Finally, the ME-based proposal can maintain high absorptionwhen it comes closer to terminate finite-difference time-domain (FDTD) domains sothat smaller physical regions can be applied, leading to palpable improvements inmemory and CPU time. The three-dimensional (3D) numerical simulations on monolayer BP THz problems have been carried out to illustrate the validity and accuracy ofthe proposal.
Keywords: Black phosphorous; complex-frequency-shifted perfectly matched layer; finite-difference time-domain; metasurface; matched Z-transform; matrix exponential.